Parameters Affecting the Efficiency of a Heat Transformer with a Particular Focus on the Heat Solution. (November 2016) - Golasi, Iacopo; Salata, Ferdinando; de Lieto Vollaro, Emanuele; Coppi, Massimo
Abstract: The heat transformer is a reverse cycle absorption machine, suitable for the direct exploitation of heat wastes and solar energy. Part of these wastes are "transformed" into thermal energy at a higher temperature than the one provided. Hence some studies concern the evaluation of the performances of the working fluids used. They must ensure a high level of efficiency which, as for the conventional absorption machines, depends on several parameters. One of these parameters is the heat solution: it is defined as the heat absorbed when a mole of a given component is mixed with the amount of the other component required to generate the desired solution at a certain temperature and pressure. This is the reason why the decision was to examine its influence with respect to machines exerting two different fluids which are generally used. The first one is NH3 -H2 O, whereas the second is H2 O-LiBr; they used as refrigerating substances ammonia and water respectively and as absorption substances water and lithium bromide. Through an analytical modeling and the processing of experimental data provided by the bibliography, it was possible to show how, for these fluids, the terms of the sensible heat represent a moderate fraction of the global energy balance, at one condition though: highly efficient recovery exchangers must be present. Moreover there were reported values of the refrigeration effect of the order of thousands of kJ/kg with satisfying responses energetically speaking. Then a high stability of the fluid NH3 -H2 O was revealed, as testified by the high value of the difference between the concentration of the refrigerator in the absorber and the concentration of the refrigerator in the generator.